Magnetically actuated mechanical stimuli on Fe3O4/mineralized collagen coatings to enhance osteogenic differentiation of the MC3T3-E1 cells. (15th April 2018) - Zhuang, Junjun; Lin, Suya; Dong, Lingqing; Cheng, Kui; Weng, Wenjian
Graphical abstract: Abstract: Mechanical stimuli at the bone-implant interface are considered to activate the mechanotransduction pathway of the cell to improve the initial osseointegration establishment and to guarantee clinical success of the implant. However, control of the mechanical stimuli at the bone–implant interface still remains a challenge. In this study, we have designed a strategy of a magnetically responsive coating on which the mechanical stimuli is controlled because of coating deformation under static magnetic field (SMF). The iron oxide nanoparticle/mineralized collagen (IOP-MC) coatings were electrochemically codeposited on titanium substrates in different quantities of IOPs and distributions; the resulting coatings were verified to possess swelling behavior with flexibility same as that of hydrogel. The relative quantity of IOP to collagen and the IOP distribution in the coatings were demonstrated to play a critical role in mediating cell behavior. The cells present on the outer layer of the distributed IOP-MC (O-IOP-MC) coating with a mass ratio of 0.67 revealed the most distinct osteogenic differentiation activity being promoted, which could be attributed to the maximized mechanical stimuli with exposure to SMF. Furthermore, the enhanced osteogenic differentiation of the stimulated MC3T3-E1 cells originated from magnetically actuated mechanotransduction signaling pathway, embodying the upregulated expression of osteogenic-related and mechanotransduction-related genes. This work therefore provides a promising strategy for implementing mechanical stimuli to activate mechanotransduction on the bone–implant interface and thus to promote osseointegration. Statement of Significance: The magnetically actuated coating is designed to produce mechanical stimuli to cells for promoting osteogenic differentiation based on the coating deformation. Iron oxide nanoparticles (IOPs) were incorporated into the mineralized collagen coatings (MC) forming the composite coatings (IOP-MC) with spatially distributed IOPs, and the IOP-MC coatings with outer distributed IOPs (O-IOPs-MC) shows the maximized mechanical stimuli to cells with enhanced osteogenic differentiation under static magnetic field. The upregulated expression of the associated genes reveals that the enabled mechanotransduction signaling pathway is responsible for the promoted cellular osteogenic differentiation. This work therefore provides a promising strategy for implementing mechanical stimuli to activate mechanotransduction on the bone–implant interface to promote osseointegration.